Émergence et registre d’action des associations pour le maintien de l’agriculture paysanne (AMAP) en périurbain : quel lien au territoire ? - Marianne Chometon (VertigO)
Agriculture, in periurban areas, is in an ambivalent situation : it is week because of the urbanisation process and in the other hand it guarantees periurban’ attractivness. By a case study we search to understand how AMAP can support agriculture in these areas. The case of Cheires AMAP (Auvergne, France) shows that the support is visible at local level by assuring producers of outlets and at the regional level by sharing information with other AMAP in order to settle new producers.